Laurel & Hardy [videorecording (DVD)]. - Laurel, Stan; Hardy, Oliver, 1892-1957 (TV classics (Platinum Disc Corporation), 2003)
A collection of 2 features and 6 silent short films, featuring "Hollywood's original comedy team" Laurel and Hardy, including "Lucky Dog," their first film.